2019
DOI: 10.1089/lgbt.2018.0256
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Potential Pre-Exposure Prophylaxis Users onto a Motivational Cascade: Identifying Targets to Prepare for Implementation in China

Abstract: Purpose: China recently commenced several pre-exposure prophylaxis (PrEP) projects, but little work has characterized potential users. This study describes awareness of, intention to use, and uptake of PrEP in a sample of men who have sex with men (MSM), a key population experiencing high rates of HIV in China. Methods: Through a cross-sectional survey administered to 708 MSM in four cities, we mapped respondents onto a Motivational PrEP Cascade. We conducted bivariable and multivariable analysis to examine fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…However, with the expiration of drug (TDF) patents, the increase in market competition, and the decrease in price of TDF in China (from around CNY 1500 to 500 per month) [34], a substantial decline in the price of PrEP is expected in the future in China. Recently, the motivational PrEP cascade was put forward and used as a conceptual tool for identifying discrepancies between willingness and behavior [35,36]. The motivational PrEP cascade involves five stages: (1) Stage 1, unwilling to take PrEP, (2) Stage 2, willing to take PrEP, (3) Stage 3, in PrEParation (i.e., seeing PrEP as accessible and planning to initiate PrEP), (4) Stage 4, in PrEP action (i.e., prescribed PrEP), and (5) Stage 5, maintenance and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the expiration of drug (TDF) patents, the increase in market competition, and the decrease in price of TDF in China (from around CNY 1500 to 500 per month) [34], a substantial decline in the price of PrEP is expected in the future in China. Recently, the motivational PrEP cascade was put forward and used as a conceptual tool for identifying discrepancies between willingness and behavior [35,36]. The motivational PrEP cascade involves five stages: (1) Stage 1, unwilling to take PrEP, (2) Stage 2, willing to take PrEP, (3) Stage 3, in PrEParation (i.e., seeing PrEP as accessible and planning to initiate PrEP), (4) Stage 4, in PrEP action (i.e., prescribed PrEP), and (5) Stage 5, maintenance and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, data for this analysis were collected prior to March 2016 and it is possible the prevalence of risk behaviours or willingness to report risk behaviours may differ in 2020. As a comparison point, a recent cross‐sectional analysis published in 2019 used a modified version of the USPHC PrEP eligibility assessment tool and found 45.6% of surveyed MSM in China met the eligibility requirements [32]. Additional studies should replicate this approach in different settings to assess the appropriateness of a set of guidelines in their specific context.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies among potential PrEP users identified the need for gain-framed messaging when promoting PrEP to avoid such stigma [24,54]. Our training therefore adopted a sex-positive approach to empower lay HIV workers to accurately communicate potential benefits of PrEP and avoid stigmatizing approaches (such as promoting PrEP as a strategy for people with "very high risk" of HIV) [24,53,54] as a stigma-mitigation strategy. As China is on the cusp of PrEP implementation, it is critical to devise strategies to integrate PrEP into health services without introducing PrEP stigma against potential users.…”
Section: Discussionmentioning
confidence: 99%